TANAH SANGKOL SEBUAH GENEOLOGI ECO-TEOLOGI PELESTARI LINGKUNGAN MANUSIA SUMENEP - A Zahid, A Zahid; Chakim, Abdulloh; Ayu, Agustini Kala (Jurnal Ilmiah Sosiologi Agama (JISA), 2024)
The agrarian problem in Sumenep has become an interesting issue in recent years. Many investors, both from inside and outside, are coming in, from the tanah sangkol becoming shrimp ponds, beaches that are starting to disappear, and rice fields that are starting to be planted with iron for hotels and housing. In fact, Sumenep, which has historical roots in the genealogy of eco-theology in environmental conservation, must now be questioned. Qualitative research as a method for obtaining in-depth data using observation and deep interview, the data obtained will be analyzed by data collection, data reduction, and drawing conclusions. The results of this research show that the eco-theological genealogy of the Sumenep community in preserving the environment can be seen in the form of the socio-historical genealogy of Syeh Ahmad Baidlawi or known as kiai Katandur ,who preaches an agricultural approach. Apart from that, the identity of the people of Sumenep is part of their "Kemadura" identity tanah sangkol is a source of pride for the people of Sumenep, one way of caring for the land and the environment is now starting to be questioned.